Improving Multi Access Interference Suppression in Optical CDMA by using all-Optical Signal Processing - T. B. Osadola (Telfor Journal, 2013)

(untitled)
This paper presents the study of a novel all-optical method for processing optical CDMA signals towards improving suppression of multi access interference. The main focus is on incoherent OCDMA systems using multiwavelength 2D-WH/TS codes generated using FBG based encoders and decoders. The MAI suppression capabilities based on its ability to eliminate selective wavelength pulse processing have been shown. A novel transmitter architecture that achieves up to 3dB power saving was also presented. As a result of hardware savings, processing cost will be significantly reduced and power budget improvement resulted in improved performance.